3. The theology of politics : toward a Latin American ecclesiology - Dussel, Enrique D. (Orbis Books, 2021)
In this chapter I would like to dwell on the following theme: a Latin American ecclesiology .Here I will deal with another article of the creed: "I believe in the Holy Spirit, in the Holy Church"; this is how the most ancient of creeds states it (Denzinger, 1963; no. II). I intend to go into the theology of politics. The question we should ask ourselves is: What is the function of the church in world history? Or, more simply: What is the function of the church? On previous occasions I have pointed out that to deal with the history of the church is to deal with ecclesiology. I want to treat this theme in more depth.